Effect of Non‐Volatile Constituents of Elsholtzia ciliata (Thunb.) Hyl. from Southern Vietnam on Reactive Oxygen Species and Nitric Oxide Release in Macrophages. Issue 1 (17th December 2020) - Nguyen, Dieu T. X.; Tran, Hung; Schwaiger, Stefan; Stuppner, Hermann; Marzocco, Stefania
Abstract: The extract of Elsholtzia ciliata aerial parts was subjected to bio‐guided isolation using the intercellular ROS reduction in J774A.1 macrophages to monitor the anti‐oxidative activity. Fifteen compounds were isolated from the active fractions including eleven flavonoids (vitexin, pedalin, luteolin‐7‐ O‐β ‐d ‐glucopyranoside, apigenin‐5‐ O‐β ‐d ‐glucopyranoside, apigenin‐7‐ O‐β ‐d ‐glucopyranoside, chrysoeriol‐7‐ O‐β ‐d ‐glucopyranoside, 7, 3′‐dimethoxyluteolin‐6‐ O‐β ‐d ‐glucopyranoside, luteolin, 5, 6, 4′‐trihydroxy‐7, 3′‐dimethoxyflavone, 5‐hydroxy‐6, 7‐dimethoxyflavone (compound 13 ), 5‐hydroxy‐7, 8‐dimethoxyflavone); three hydroxycinnamic acid derivatives (caffeic acid, 4‐( E )‐caffeoyl‐l ‐threonic acid, 4‐ O ‐( E )‐ p‐ coumaroyl‐l ‐threonic acid) and one fatty acid (α‐linolenic acid). The biological evaluation of these compounds (10–2.5 μm ) indicated that all of them exerted good antioxidant and anti‐inflammatory activities, in particular compound 13 . Abstract :